Sequence of facies at a Holocene storm-dominated regressive barrier at Praia de Leste, southern Brazil - de Souza, Maria Cristina; Angulo, Rodolfo José; Assine, Mario Luis [UNESP]; de Castro, David Lopes (Elsevier, 2012)
Along the coast at Praia de Leste, southern Brazil (25° 41' S latitude), a positive sedimentary budget and a lowering of the sea level following the postglacial maximum has given rise to a progradational strandplain barrier that is 3-5. km wide. Sand quarries that lie 3.5. km from the present-day coastline have provided material from exceptional outcrops of 75% of the sequence of Holocene barrier facies. Five facies associations have been identified, which correspond to the inner shelf, the lower, middle and upper shorefaces, and the foreshore. The architecture of the facies shows a regressive sequence that overlies an erosional surface and downlapping Pleistocene sediments. At Praia de Leste, the facies association has a thickness of 14. m and is deposited between 2. m above and 12. m below mean paleo sea level. The barrier corresponds to a coastal environment that is characterised by medium to low wave energy under the additional influence of episodic storm events. The sequence at the Praia de Leste barrier differs from the sequence of clastic shoreline facies found elsewhere in two main ways. The first difference is the high content of fine sediment and plant debris, released at around the same time as the formation of the barrier from large estuarine systems, and the second is the predominance on the middle and lower shorefaces of swaley cross-stratified sand facies with abundant plant debris. We also describe two further characteristics of the barrier at Praia de Leste. First, the swaley cross-stratified sand represents a component of onshore transport that resulted in the accumulation of sediment transported from the shelf. Second, the beach step has been well preserved, thereby allowing the continuous tracing of seaward-dipping, low-angle cross-stratification to a sigmoidal cross-stratified beach-step sandy facies. Finally, we have herein been able to improve the precision of the sequence of formation of the depth of the facies, by making reference to paleo sea level during the formation of the barrier, rather than to present-day mean sea level. © 2011 Elsevier B.V..
Keywords: Beach step; Clastic strandplain; Paleo-bathymetry; Subtropical barrier; Swaley cross stratification; Wave dominated environments